2016
DOI: 10.1073/pnas.1605501113
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide detoxification is a key mechanism for growth of ammonia-oxidizing archaea

Abstract: Ammonia-oxidizing archaea (AOA), that is, members of the Thaumarchaeota phylum, occur ubiquitously in the environment and are of major significance for global nitrogen cycling. However, controls on cell growth and organic carbon assimilation by AOA are poorly understood. We isolated an ammonia-oxidizing archaeon (designated strain DDS1) from seawater and used this organism to study the physiology of ammonia oxidation. These findings were confirmed using four additional Thaumarchaeota strains from both marine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
179
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 38 publications
5
179
0
2
Order By: Relevance
“…However, despite the large amount of transporters encoded in the genome of N. viennensis (13), we have so far not been able to identify alternate energy or carbon sources in growth experiments. In addition, Kim et al (47) have convincingly shown that the dependency of N. viennensis and other strains on small amounts of organic acids (16,17,48) can be overcome by reducing reactive oxygen species in the medium. Consequently, based on growth experiments and genomic predictions, all AOA currently in pure culture can grow strictly autotrophically.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the large amount of transporters encoded in the genome of N. viennensis (13), we have so far not been able to identify alternate energy or carbon sources in growth experiments. In addition, Kim et al (47) have convincingly shown that the dependency of N. viennensis and other strains on small amounts of organic acids (16,17,48) can be overcome by reducing reactive oxygen species in the medium. Consequently, based on growth experiments and genomic predictions, all AOA currently in pure culture can grow strictly autotrophically.…”
Section: Resultsmentioning
confidence: 99%
“…Keto acids have been reported to be chemical scavengers in both bacterial culture and mammalian cells 25,26 . A plausible reaction pathway for the generation of acetate could involve the nucleophilic attack of pyruvate by the reactive oxygen species generated from hydrogen peroxide (H 2 O 2 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the very little dose of organic matters like 0.20 mg/L of yeast extract or 2 mM acetate inhibited the growth of Nitrosocaldus yellowstonii (De La Torre et al, 2008). Despite facts above, organic matters could sometimes stimulate the growth of AOA (Bayer et al, 2016;Kim et al, 2016;Lehtovirta-Morley et al, 2014;Sauder et al, 2017). The phenomenon that the growth rate of Nitrososphaera viennensis increased significantly and its cell generation got shortened by 11.5 times when 0.10 mM pyruvate was added, was misinterpreted as mixtrophy (Tourna et al, 2011), and was recently explained as a hydrogen peroxide detoxification mechanism .…”
Section: Organic Matters Leading To the Niche Segregation Of Aoa And Aobmentioning
confidence: 99%
“…As chemolithoautotrophic organisms, some AOA tend to be inhibited by organic matters Kim et al, 2016;Könneke et al, 2005;Lehtovirta-Morley et al, 2014). For example, the very little dose of organic matters like 0.20 mg/L of yeast extract or 2 mM acetate inhibited the growth of Nitrosocaldus yellowstonii (De La Torre et al, 2008).…”
Section: Organic Matters Leading To the Niche Segregation Of Aoa And Aobmentioning
confidence: 99%
See 1 more Smart Citation